Analisis Teori Hypodermic Needle Pada Iklan Sirup Marjan Di Bulan Ramadhan Tahun 2023 - Wawan Sopiyan; Solimin solimin; Muhammad Qomarullah; Naim Ulfinuwa; Indah Nurjanah (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2023)
This study seeks to analyze how the hypodermic needle theory works on Marjan syrup advertisements in the month of Ramadan 2023. The research was conducted by observing marjan syrup advertisements both aired on television and Marjan Badoin's YouTube account. Data collection techniques were carried out by collecting data about mass communication, especially about the hypodermic needle theory, relevant journals and books as well as Marjan Syrup advertising videos on television and Marjan Boudoin's Youtube account. This study uses a descriptive qualitative approach. The results of the study concluded that the mass media, in this case television and YouTube, which display advertisements in the form of Audio Visual Marjan Syrup messages play a strong role in influencing affectively, cognition and behavior of the audience/society. Especially for people with an undeveloped level of education, the audience/society is more easily influenced because the majority of television viewers in Indonesia are people with a level of education that is not yet well established and children who have not received higher education. third, the message conveyed is easier to understand, Audio visual shows are more interesting, more accepted and easier to understand by the public/public. Viewers don't have to bother reading to understand what messages the advertisements convey on television or YouTube channels.